Cultivating Intercultural Communication Through The Indonesian Language and Cultural Understanding for Misamis University Students - Ade Tuti Turistiati; Apik Anitasari Intan Saputri; Farrel Ega Saputra; Dimas Rizky Pratama (STMIK Royal, 2026)
Abstract: This community service aimed to improve participants from Misamis University, Philippines' understanding of Indonesian culture, the Indonesian language and the position of English used in Indonesia. The program was conducted through two online training sessions via Zoom meetings. The implementation followed five stages: Training Needs Analysis, Planning, Training Implementation, Evaluation, and Documentation. The Training Needs Analysis identified participants’ needs related to Indonesian cultural knowledge. Based on the findings, training materials and learning activities were designed during the planning stage. The implementation stage consisted of interactive sessions introducing Indonesian cultural diversity, traditions, and values. Evaluation was conducted through participant feedback and assessment of learning outcomes, while documentation recorded the entire process and results. The findings demonstrated that the program effectively enhanced participants’ understanding of Indonesian culture. Evaluation results revealed that 92% of participants indicated that they were motivated, felt confident, and developed a positive self-image regarding their understanding and appreciation of Indonesian culture. These results suggest that online cultural training can be an effective way to promote cultural awareness and empower participants to engage more confidently with Indonesian cultural values. Keywords: cultural understanding; indonesian language; intercultural communication; misamis university; philippines. Abstrak: Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman peserta dari Misamis University mengenai budaya Indonesia, bahasa Indonesia, serta posisi bahasa Inggris yang digunakan di Indonesia. Program ini dilaksanakan melalui dua sesi pelatihan daring menggunakan Zoom Meeting. Pelaksanaan kegiatan dilakukan melalui lima tahapan, yaitu: Analisis Kebutuhan Pelatihan (Training Needs Analysis), Perencanaan, Pelaksanaan Pelatihan, Evaluasi, dan Dokumentasi. Tahap Analisis Kebutuhan Pelatihan dilakukan untuk mengidentifikasi kebutuhan peserta terkait pengetahuan tentang budaya Indonesia. Berdasarkan hasil analisis tersebut, materi pelatihan dan aktivitas pembelajaran dirancang pada tahap perencanaan. Tahap pelaksanaan terdiri atas sesi-sesi interaktif yang memperkenalkan keberagaman budaya, tradisi, dan nilai-nilai yang dimiliki Indonesia serta bahasa Indonesia. Selanjutnya, evaluasi dilakukan melalui umpan balik peserta dan penilaian hasil belajar, sedangkan dokumentasi digunakan untuk merekam seluruh proses dan hasil kegiatan. Hasil kegiatan menunjukkan bahwa program ini berhasil meningkatkan pemahaman peserta mengenai budaya Indonesia. Hasil evaluasi mengungkapkan bahwa 92% peserta menyatakan termotivasi, merasa lebih percaya diri, serta mengembangkan citra diri yang positif terkait pemahaman dan apresiasi mereka terhadap budaya Indonesia. Temuan ini menunjukkan bahwa pelatihan budaya secara daring dapat menjadi metode yang efektif untuk meningkatkan kesadaran budaya serta memberdayakan peserta agar lebih percaya diri dalam memahami dan mengaplikasikan nilai-nilai budaya Indonesia. Kata Kunci: bahasa indonesia; komunikasi antarbudaya; misamis university; pemahaman budaya; philippines